2012
DOI: 10.15580/gjss.2012.3.gjss1223
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Domestic Violence among Women in Ogun State, Nigeria

Abstract: This study assessed domestic violence among women in Ogun State. Data were collected using structured interview guide. Purposively sampling technique was used to select 220 respondents in two zones of Ogun State Agricultural Development Programme. Data were analyzed using descriptive statistics, Pearson Product Moment Correlation (PPMC). Findings showed that the mean age of respondents was 48.73 years, while the mean household size was 6 persons. Also, 41% of the respondents were Christians. Few, (26.20%) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 6 publications
(4 reference statements)
0
15
0
Order By: Relevance
“…In addition, if and when these girls enter marital unions, they are also likely to remain susceptible to IPV because they are unlikely to report or say “no” to what they consider appropriate behavior. This also shows why many victims of DV simply keep quiet when they are abused by their husbands (Aborisade, 2012; Ashimolowo & Otufale, 2012).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, if and when these girls enter marital unions, they are also likely to remain susceptible to IPV because they are unlikely to report or say “no” to what they consider appropriate behavior. This also shows why many victims of DV simply keep quiet when they are abused by their husbands (Aborisade, 2012; Ashimolowo & Otufale, 2012).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…So severe is the problem of DV that studies have documented cases against pregnant women (Efetie & Salami, 2007; Envuladu et al, 2012; Project Alert, 2011). Yet, most cases of DV suffered by women are unreported and nothing is done by the victims beyond silence and hoping that the situation will change (Aborisade, 2012; Ashimolowo & Otufale, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Same were reported by Project Alert (2007) and AfrolNews (2007). However, Ashimolowo & Otufale (2012) had contrary findings as they revealed that majority of their respondents in Ogun State of Nigeria never experienced domestic violence.…”
Section: Introductionmentioning
confidence: 94%
“…In USA, women experienced about 4.8million intimate partner-related physical assaults and rape and even in Ghana, SV tops the list of domestic violence. In Nigeria, despite the fact that CV especially among the elites is underreported (Moronkola, 2003;Adewale, 2009;Ashimolowo & Otufale, 2012;Adebayo & Kolawole, 2013;Adebayo, 2013) for fear of divorce, abuser's retaliation, stigmatization and loss of economic support, yet, the situation is not different. Pearce (1992) specifically found that in Ile-Ife (the homeland of the Yorubas), wife assault is not only common, but highly visible.…”
Section: Introductionmentioning
confidence: 99%
“…It is a term used to collectively refer to violent acts that are primarily or exclusively committed against women and physical abuse is one of the commonest forms of abuse [2]. It is a form of gender based violence which can be described as any harm that is perpetrated against a person as a result of inequalities that are based on gender roles [3]. The united nations declaration on the elimination of violence against women in 1993 defines violence against women as any act of gender based violence that results in or is likely to result in physical, sexual or psychological harm of suffering of women including threats of such acts, coercion or arbitrary deprivation of liberty whether occurring in private or public life [4].…”
Section: Introductionmentioning
confidence: 99%